From Play to Progress: Illuminating Students’ Interest in Digital Game-Based Learning - Hasania, Luluk Masluhatil; Rakhmawati; Fithrijah, Siti Salisa (ICONELT, 2024)
This study investigates the role of digital game-based learning (DGBL) in increasing students’ interest and motivation in English language learning. The study is based on 33 students from class 8E at SMPN 1 Lamongan and uses qualitative methods, namely observation and interviews to identify factors that influence students’ engagement with digital games in the classroom. The findings reveal that DGBL significantly increases student motivation and comprehension of English materials. However, challenges such as the need for adequate technological resources and alignment of games with educational objectives are noted. Teachers perceive that DGBL promotes higher enthusiasm and interactive learning, but emphasize that careful planning and effective facilitation are crucial for successful implementation. The study provides important insight into the integration of technology in education and highlights the importance of the DGBL method in improving students’ motivation and engagement.